2021
DOI: 10.1371/journal.pone.0254407
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing identifies novel structural variant in a large Indian family affected with X-linked agammaglobulinemia

Abstract: X—linked agammaglobulinemia (XLA, OMIM #300755) is a primary immunodeficiency disorder caused by pathogenic variations in the BTK gene, characterized by failure of development and maturation of B lymphocytes. The estimated prevalence worldwide is 1 in 190,000 male births. Recently, genome sequencing has been widely used in difficult to diagnose and familial cases. We report a large Indian family suffering from XLA with five affected individuals. We performed complete blood count, immunoglobulin assay, and lymp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…82 It is the most prevalent primary immunodeficiency in males, affecting approximately one in every 100,000 male newborns in the United States 83 with varying statistics worldwide. 84 Furthermore, XLA accounts for 85% of all early B cell defects. 85 It arises from the impaired function of the critical B cell receptor (BCR) protein, Bruton's Tyrosine Kinase (BTK).…”
Section: X-linked Agammaglobulinemia (Xla)mentioning
confidence: 99%
See 1 more Smart Citation
“…82 It is the most prevalent primary immunodeficiency in males, affecting approximately one in every 100,000 male newborns in the United States 83 with varying statistics worldwide. 84 Furthermore, XLA accounts for 85% of all early B cell defects. 85 It arises from the impaired function of the critical B cell receptor (BCR) protein, Bruton's Tyrosine Kinase (BTK).…”
Section: X-linked Agammaglobulinemia (Xla)mentioning
confidence: 99%
“…X‐linked agammaglobulinemia (XLA) disorder is characterized by a block in early B cell development, leading to a deficiency of circulating mature B cells and antibodies 82 . It is the most prevalent primary immunodeficiency in males, affecting approximately one in every 100,000 male newborns in the United States 83 with varying statistics worldwide 84 …”
Section: Precision In Practice: Highlighting Gene Therapy Innovations...mentioning
confidence: 99%
“…However the whole genome sequencing (WGS) has the ability to identify variants in difficult-to-diagnose cases. Recently, our group has identified ~ 5 Kb deletion in the primary immunodeficiency disorder (PID) patients that could not be identified using whole exome sequencing [ 19 ]. Also, Thaventhiran et al has identified eight SVs by performing the WGS of 1318 patients affected with PID, that could be missed using the WES [ 20 ].…”
Section: Introductionmentioning
confidence: 99%